2016
DOI: 10.1115/1.4034267
|View full text |Cite
|
Sign up to set email alerts
|

An Industry Case Study: Investigating Early Design Decision Making in Virtual Reality

Abstract: The research presented here describes an industry case study of the use of immersive virtual reality (VR) as a general design tool with a focus on the decision making process. A group of design and manufacturing engineers, who were involved in an active new product development project, were invited to participate in three design reviews in an immersive environment. Observations, interviews, and focus groups were conducted to evaluate the effect of using this interface on decision making in early product design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 12 publications
1
65
0
Order By: Relevance
“…For example, Liu et al (2014) showed how virtual facility prototypes allow reviewers to deeper understand the implications of design decisions. Van den Berg et al (2017) reviewed the literature to explore how design reviews can be supported by immersive virtual environments to communicate design intents as well as to ask for design feedback, allowing designers and clients to navigate through and comment on a design in progress. Exploration from a user perspective, participation in solution-finding and feedback on a design proposal are the patterns they identified in relation to VR implementation in collaborative design reviews.…”
Section: Immersive Virtual Reality In Usability-focused Design Reviewsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Liu et al (2014) showed how virtual facility prototypes allow reviewers to deeper understand the implications of design decisions. Van den Berg et al (2017) reviewed the literature to explore how design reviews can be supported by immersive virtual environments to communicate design intents as well as to ask for design feedback, allowing designers and clients to navigate through and comment on a design in progress. Exploration from a user perspective, participation in solution-finding and feedback on a design proposal are the patterns they identified in relation to VR implementation in collaborative design reviews.…”
Section: Immersive Virtual Reality In Usability-focused Design Reviewsmentioning
confidence: 99%
“…The implementation of virtual reality systems and the possibility to walk through the virtual facility prototype from the user perspective might also improve the engagement of stakeholders in design review and their participation in solution-finding processes (Van den Berg et al, 2017). Virtual reality, in fact, enables a more qualitative representation of spaces from a user perspective showing them in full-scale and with the possibility to walk through them as a prospective end-user (Castronovo et al, 2013) thus supporting stakeholder engagement presenting spatial information in a more engaging manner, giving users a better sense of spatial (i.e., scale, distance and adjacency) and visual (i.e., appearance and view) factors (Eastman et al 2011;Shen et al 2012;Liu, 2017).…”
Section: Immersive Virtual Reality In Usability-focused Design Reviewsmentioning
confidence: 99%
See 3 more Smart Citations